2006
DOI: 10.1161/01.res.0000197851.11031.9c
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effects of the Putative T-Type Calcium Channel Antagonist Mibefradil Are Mediated by the L-Type Calcium Channel Ca v 1.2

Abstract: Abstract-The role of T-type Ca 2ϩ channels for cardiovascular physiology, in particular blood pressure regulation, is controversial. Selective blockade of T-type Ca 2ϩ channels in resistance arteries has been proposed to explain the effect of the antihypertensive drug mibefradil. In the present study, we used a third generation, time-and tissue-specific conditional knockout model of the L-type Ca 2ϩ channel Ca v 1.2 (Ca v 1.2 SMAKO mice) to genetically dissect the effects of mibefradil on T-and L-type Ca 2ϩ ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 24 publications
(29 reference statements)
1
58
0
Order By: Relevance
“…Among the L-type Ca 2ϩ channels, the Ca v 1.2 (CACNA1C) channel is the dominant isoform in vascular smooth muscle and therefore appears to play an important role in regulating vascular tone and arterial constriction (2,45). Currently, the major targets of dihydropyridine Ca 2ϩ channel blockers as antihypertensive drugs are the Ca v 1.2 channels expressed in vascular smooth muscle (43,66). Therefore, the specific expression of Ca v 1.2 is an important characteristic of vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Among the L-type Ca 2ϩ channels, the Ca v 1.2 (CACNA1C) channel is the dominant isoform in vascular smooth muscle and therefore appears to play an important role in regulating vascular tone and arterial constriction (2,45). Currently, the major targets of dihydropyridine Ca 2ϩ channel blockers as antihypertensive drugs are the Ca v 1.2 channels expressed in vascular smooth muscle (43,66). Therefore, the specific expression of Ca v 1.2 is an important characteristic of vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…This later experiment endeavored to "pharmacologically reproduce" the L-channel conditional knockout model established by Moosmang et al 7 and to shed light on the use of combined L-and T-channel blockade in patients on existing CCB therapy.…”
Section: Study Protocolmentioning
confidence: 99%
“…Recently, Moosmang et al, 7 using a conditional L-channel knockout mouse model, demonstrated a loss of mibefradil's vasomotor effects, including impairment of its blood pressurelowering effect and a reduction in its inhibition of vasoconstrictor effects in a hindlimb perfusion model. Appropriately, these researchers concluded that, in their mouse model, vasomotor effects of mibefradil were mediated exclusively via the L-channel.…”
Section: Role Of T-channels In the Vasculaturementioning
confidence: 99%
“…The anti-proliferative and cytotoxic actions of pimozide may be mediated via other complex mechanisms and may not involve T-type channel blockade (17). Mibefradil has also been reported to inhibit cell proliferation through an association with cell swelling and the inhibition of volume-sensitive Cl -channels (27,28) or several other ion channels (29)(30)(31), in addition to a mechanism via the inhibition of T-type channels. Flunarizine, which has been reported to be a T-type antagonist (32), also produces its anti-apoptotic action via the direct inhibition of lipid peroxidation and mitochondrial permeability transition (33).…”
Section: Discussionmentioning
confidence: 99%